2003
DOI: 10.1016/s0167-4889(03)00082-x
|View full text |Cite
|
Sign up to set email alerts
|

A cell-free binding assay maps the LSP1 cytoskeletal binding site to the COOH-terminal 30 amino acids

Abstract: The leukocyte specific protein 1 or LSP1 is a multi functional protein involved in such divers biological processes as the regulation of neutrophil motility, chemotaxis, adhesion and membrane immunoglobulin M (mIgM) mediated apoptosis of B-lymphocytes. The 330-amino-acid mouse LSP1 protein contains a high-affinity F-actin binding site and in intact cells localizes to the F-actin filament containing cytoskeleton. Here we use a high-speed F-actin co sedimentation assay and transfection experiments in the LSP1- T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Although it is known that LSP1 interacts with actin filaments (Klein et al, 1990;Wong et al, 2003;Zhang et al, 2001), the mechanisms underlying LSP1 function in the regulation of actin-driven processes are, as yet, poorly defined. Before discussing potential scenarios describing LSP1 function, our previous study (Maxeiner et al, 2015) and the findings described here clearly indicate that one possible mechanism for LSP1 function requires its interaction with myosin1e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is known that LSP1 interacts with actin filaments (Klein et al, 1990;Wong et al, 2003;Zhang et al, 2001), the mechanisms underlying LSP1 function in the regulation of actin-driven processes are, as yet, poorly defined. Before discussing potential scenarios describing LSP1 function, our previous study (Maxeiner et al, 2015) and the findings described here clearly indicate that one possible mechanism for LSP1 function requires its interaction with myosin1e.…”
Section: Discussionmentioning
confidence: 99%
“…The amino-terminal half of LSP1 incorporates Ca 2+ -binding sites and a coiled-coil region (Jongstra et al, 1988;Klein et al, 1989), suggesting that Ca 2+ signalling and dimerization could regulate LSP1 function. The carboxy-terminal half incorporates a caldesmon-like region having a weaker F-actin-binding activity Zhang et al, 2001) and two villin headpiece-like sequences, which primarily mediate the interaction of LSP1 with F-actin (Klein et al, 1990;Wong et al, 2003;Zhang et al, 2001). We have demonstrated that the carboxy-terminal half of LSP1 directly interacts with the SH3 domain of the molecular motor myosin1e through the noncanonical SH3-binding site AGDMSKKS (Maxeiner et al, 2015).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The basic C-terminal domain contains amino acid sequences homologous to two known F-actin binding proteins, caldesmon and the villin headpiece (36,37). Although LSP1 is an F-actin binding protein, it is also a very important regulator of microfi lamentous cytoskeleton dynamics (34).…”
Section: Discussionmentioning
confidence: 99%
“…LSP1 is an F-actin binding protein involved in cell motility, cell adhesion, and IgM internalization (34)(35)(36)(37). The caldesmonlike (CI and CII) and villin-like (VI and VII) are two domains on LSP1 that bind F-actin to facilitate neutrophil motility (38).…”
Section: Dc-sign Binds To a Distinct Domain Of Lsp1 Between Amino Acimentioning
confidence: 99%